2008
DOI: 10.1002/app.27861
|View full text |Cite
|
Sign up to set email alerts
|

Study of different effects on foaming process of biodegradable PLA/starch composites in supercritical/compressed carbon dioxide

Abstract: Microcellular foaming of biodegradable and biocompatible PLA/starch composites in supercritical/compressed CO 2 has been studied. The purpose of this study is to explore the potential application of this kind of materials in medical materials or drug containers. The rate of CO 2 uptake and CO 2 equilibrium concentration in PLA/starch composites were studied by performing sorption and desorption experiments. The effects of a series of variable factors, such as saturation time and saturation temperature on the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 29 publications
2
23
0
Order By: Relevance
“…Overall, the lower saturation pressures (up to 2.76 MPa) resulted in more uniform microcellular structures. Higher saturation pressure resulted in the structures becoming inhomogeneous and drastically deteriorated, owing to the polymer's rapid diffusion of CO 2 and the CO 2 -induced crystallization in PLA from the plasticizing effect of gas at high concentrations [15,30]. These results correlated with those reported by other investigators who found that an optimal saturation pressure for foaming PLA exists.…”
Section: Morphology and Expansion Ratio Of Microcellular Neat Plasupporting
confidence: 80%
See 1 more Smart Citation
“…Overall, the lower saturation pressures (up to 2.76 MPa) resulted in more uniform microcellular structures. Higher saturation pressure resulted in the structures becoming inhomogeneous and drastically deteriorated, owing to the polymer's rapid diffusion of CO 2 and the CO 2 -induced crystallization in PLA from the plasticizing effect of gas at high concentrations [15,30]. These results correlated with those reported by other investigators who found that an optimal saturation pressure for foaming PLA exists.…”
Section: Morphology and Expansion Ratio Of Microcellular Neat Plasupporting
confidence: 80%
“…By contrast, foam structures became inhomogeneous and cell size decreased with an increase in saturation pressure, owing to the rapid diffusion of CO 2 out of the polymer. As a result, the density of the foamed sample was almost similar to that of unfoamed material [15,30]. Furthermore, it is recognized that the solubility and diffusivity of gas in semi-crystalline polymers are a function of the degree of crystallinity because gas does not dissolve in the crystallites [22,[31][32][33].…”
Section: Morphology and Expansion Ratio Of Microcellular Neat Plamentioning
confidence: 99%
“…Two main approaches have been applied to overcome these problems-blending or chemical modification. Starch can be blended with biodegradable polymers such as PHB (Lai et al 2006;Thire et al 2006), PLA (Jang et al 2007;Hao et al 2008;Ning et al 2008), PCL (Wang et al 2005;Rosa et al 2006;Kim et al 2007;Sarazin et al 2008) and chitosan (Xu et al 2005;Durango et al 2006;Nakamatsu et al 2006). Fabrication of composites based on organic or inorganic reinforcement is another possible solution to improve the performance of starch films.…”
Section: Starchmentioning
confidence: 97%
“…Microcellular plastics (MCPs) are a kind of foam plastics used to fabricate microvoids or cells in the polymer matrix with the cell density in the order of 10 8 cells/cm 3 or higher and cell sizes in the order of 10 µ m or less (from 5 to 100 µ m typically) [7,8] . Generally, the physical blowing agents for processing MCPs are inert gases such as the physical blowing agents of supercritical fl uid (SCF, i.e., carbon dioxide or nitrogen [8] ).…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the physical blowing agents for processing MCPs are inert gases such as the physical blowing agents of supercritical fl uid (SCF, i.e., carbon dioxide or nitrogen [8] ). Compared with dense polymer, the major purpose of MCPs is similar to other foamed plastics, that is, to provide a substantial reduction in weight combined without sacrifi cing materials properties.…”
Section: Introductionmentioning
confidence: 99%